HISTORICAL ANALYSIS AND LEGAL FEATURES OF CORRUPTION PREVENTION IN UKRAINE - Maxim Zabarny; Dariya Vitiuk (Journal of International Legal Communication, 2022)
The article emphasized that corruption in Ukraine is the number one problem throughout the history of the formation and functioning of Ukrainian statehood. The catch phrase uttered two hundred years ago by the historian Karamzin, reflecting the essence of the Ukrainian state in one phrase "Steal", is still relevant today. The main problem of corruption in Ukraine is that the laws themselves lay the corruption space, due to the ambiguity of their interpretation and wording. Traditionally, after the adoption of any program, concept, law in the field of combating corruption, additional formal support takes place in the form of mandatory publication in the media, and the most interesting thing in each structure is the creation of public councils that do not perform those functions, which are assigned to them, and historical features show and prove, that any action aimed at combating corruption gains the opposite result. Today there is no unified understanding in the prevention of this phenomenon, due to the fact that it is necessary to start with a change in the psychology of people, from the moral and political climate in a society that does not see or do not trust the state guidelines that exist today. Due to this, a public opinion has been formed that the government itself is corrupt at all levels and in order for a turning point in the consciousness of the people to occur, it is necessary to show the inevitability of punishment. Only after that will there be a really intolerant attitude towards corruption in society, when the government itself will increase its responsibility to society, when the judicial system will be completely independent of power then and there will be a certain shift in the prevention of corruption. It was concluded that it is necessary that the fight against corruption should have a systemic form where the main principles in the fight against corruption should be the legality and openness of power. The most important thing is that criminal offenses of a corrupt nature always go unpunished due to what they have committed.